2020
DOI: 10.1111/avsc.12534
|View full text |Cite
|
Sign up to set email alerts
|

Forest patch size predicts seed bank composition in urban areas

Abstract: Questions: As urban areas expand around the world, understanding how to restore and maintain forests within the urban environment becomes increasingly important. Given that a comprehensive understanding of regeneration dynamics is critical to designating appropriate management interventions we ask the following: how does regeneration, vis-à-vis the buried seed bank, vary in heterogenous urban forests? And, can forest patch size be used to predict regeneration and consequent management interventions? Location: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Results from our regeneration regression models also confirmed that more isolated plots (i.e., further from adjacent forest) harbored higher proportions of non‐native tree seedlings—a trend also detected in the buried seed banks of the same plots (Doroski, Duguid, & Ashton, 2020). Isolation was also was highly correlated with edge‐to‐interior ratio, area, and forest age (correlation coefficient > 0.50; Appendix S1: Figure S2).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Results from our regeneration regression models also confirmed that more isolated plots (i.e., further from adjacent forest) harbored higher proportions of non‐native tree seedlings—a trend also detected in the buried seed banks of the same plots (Doroski, Duguid, & Ashton, 2020). Isolation was also was highly correlated with edge‐to‐interior ratio, area, and forest age (correlation coefficient > 0.50; Appendix S1: Figure S2).…”
Section: Discussionsupporting
confidence: 68%
“…The most important canopy tree and sapling species in small patches included a mixture of native and non‐native species. Two of these non‐native species (black locust and tree of heaven) were also the most abundant and frequent germinants in a buried seed bank study conducted at the same sites just a year prior (Doroski, Duguid, & Ashton, 2020). When canopy tree composition is similar to composition in the buried seed bank, forests are presumed to be in an earlier successional stage (Grime, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, the studies took an environmental justice or environmental equity approach, seeking to understand how access Beaulieu et al, 2014;Biehler et al, 2019;Carmichael et al, 2019;Harada et al, 2020;Larson & Perrings, 2013;Prudencio & Null, 2018;Reisinger et al, 2019;Sicard et al, 2018;Taguchi et al, 2020;Wang et al, 2014;Zhang et al, 2020 Crompton, 2007;Davis et al, 2017;Dronova et al, 2018;Evenson et al, 2013;Gerken Golay et al, 2016;Larson et al, 2016;Loeb, 2006a Doroski, Duguid, & Ashton, 2020;Escobedo et al, 2010;Jennings et al, 2019;Johnson & Handel, 2016;Lovasi et al, 2013;Nesbitt et al, 2017;Roman et al, 2021;Sicard et al, 2018;Watkins et al, 2017 Vacant land Wildlife habitat, biodiversity, climate regulation, stormwater management Physical disorder, poor health outcomes, safety concerns Anderson & Minor, 2019;Gardiner et al, 2013;Kremer et al, 2013 Other green space (turf, prairies, urban greening, urban green space)…”
Section: Ecosystem Services Associated With Nature-based Solutionsmentioning
confidence: 99%